[Hraunsfjarðarvatn on Snæfellsnes Peninsula] - Streng, Evelyn Fiedler (1975)
Photograph of Hraunsfjarðarvatn on Snæfellsnes Peninsula. The blue fjord sits at the center of the photograph, surrounded by green mountains in the background. Dark, rocky land surrounds the edges of the photograph along its sides. White boat wakes cross the bottom of the photograph. A white, wispy cloud sits at the top of the photograph, obscuring the mountain behind it.